Karakteristik mi pati sagu dengan penambahan hidrokoloid dari kolang-kaling dan porang - Erika Meiliana Sari; Feri Kusnandar; Tjahja Muhandri (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Sago noodles are made from sago starch. Low cooking loss and high elongation are the characteristics of sago noodles that are preferred. These qualities can be enhanced by adding hydrocolloids like sugar palm fruit or konjac flour, which are rich in galactomannan and glucomannan. This study evaluated the effects of adding these hydrocolloids to the pasting profile of sago starch and the characteristics of the resulting sago noodles. Sugar palm fruit paste or konjac flour (at 0.5% and 1.0%) was incorporated into the sago noodle recipe. The pasting profile was analyzed using a Rapid Visco Analyzer, while the noodle quality was assessed by measuring cooking loss, elongation, and color. The addition of sugar palm fruit paste or konjac flour lowered the peak viscosity, breakdown viscosity, setback viscosity, and final viscosity of the sago starch. Both kolang-kaling paste and porang flour have the potential to improve the cooking quality of sago noodles. Sagi noodles with these hydrocolloid additions showed reduced cooking loss, increased elongation, and improved brightness in both their dry form and after cooking. The addition of 0.5% konjac flour produced sago noodles with the lowest cooking loss of 6.68%±1.28, the highest elongation of 307.50%±2.12, and the brightest color.